Comprehensive Overview of Ketone Bodies in Cancer Metabolism: Mechanisms and Application - Ziyuan Liang; Lixian Deng; Xiaoying Zhou; Zhe Zhang; Weilin Zhao (Biomedicines)
Reprogramming energy metabolism is pivotal to tumor development. Ketone bodies (KBs), which are generated during lipid metabolism, are fundamental bioactive molecules that can be modulated to satisfy the escalating metabolic needs of cancer cells. At present, a burgeoning body of research is concentrating on the metabolism of KBs within tumors, investigating their roles as signaling mediators, drivers of post-translational modifications, and regulators of inflammation and oxidative stress. The ketogenic diet (KD) may enhance the sensitivity of various cancers to standard therapies, such as chemotherapy and radiotherapy, by exploiting the reprogrammed metabolism of cancer cells and shifting the metabolic state from glucose reliance to KB utilization, rendering it a promising candidate for adjunct cancer therapy. Nonetheless, numerous questions remain regarding the expression of key metabolic genes across different tumors, the regulation of their activities, and the impact of individual KBs on various tumor types. Further investigation is imperative to resolve the conflicting data concerning KB synthesis and functionality within tumors. This review aims to encapsulate the intricate roles of KBs in cancer metabolism, elucidating a comprehensive grasp of their mechanisms and highlighting emerging clinical applications, thereby setting the stage for future investigations into their therapeutic potential.